SPICEcore 400-480 m Major Ions SDSU - Cole-Dai, Jihong; Larrick, Carleigh (IEDA: US Antarctic Program Data Center, 2021)
Major ion concentrations in SPICEcore samples from the section of 400-480 m were measured with ion chromatography. The ions are chloride, nitrate, sulfate, sodium, potassium, magnesium, and calcium. This section was analyzed to replicate the measurement of the same section at Dartmouth College.